2013
DOI: 10.1016/j.jcis.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Micellization of dodecyltrimethylammonium bromide in water–dimethylsulfoxide mixtures: A multi-length scale approach in a model system

Abstract: The micellization in mixed solvent was studied using conductimetry, density measurements (molar volumes), and small angle neutron scattering (SANS) to explore dodecyltrimethylammonium bromide (DTABr) micelle formation throughout the entire composition range of water-dimethylsulfoxide (DMSO) mixtures. As the concentration of DMSO was increased in the mixture, the critical micelle concentration (CMC) increased, the aggregation number decreased and the ionization degree increased, until no aggregates could be det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…The densities of the AOT/isooctane reverse micelles and the AOT/ water/isooctane microemulsions with R being 2, 8,10,12,16,18,20,25,30, and 40 were measured for various concentrations at 303.15 K and are listed in Tables S1 and S2 of the Supporting Information, respectively. Among these systems the density measurements of AOT/ isooctane reverse micelles and AOT/water/isooctane microemulsions with R being 20 were carried out in very low concentrations of the solute to explore the instability condition of the reverse micelles and the microemulsions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The densities of the AOT/isooctane reverse micelles and the AOT/ water/isooctane microemulsions with R being 2, 8,10,12,16,18,20,25,30, and 40 were measured for various concentrations at 303.15 K and are listed in Tables S1 and S2 of the Supporting Information, respectively. Among these systems the density measurements of AOT/ isooctane reverse micelles and AOT/water/isooctane microemulsions with R being 20 were carried out in very low concentrations of the solute to explore the instability condition of the reverse micelles and the microemulsions.…”
Section: Methodsmentioning
confidence: 99%
“…In this paper, the micelle and microemulsions with AOT being the surfactant and isooctane being the oil and the molar ratios R being 2, 8,10,12,16,18,20,25,30, and 40 were investigated by density measurements at 303.15 K. We choose AOT as the surfactant in this study not only for its wide practical applications 20−23 but also for the large amount of information about it accumulated in the previous extensive studies. 24−27 The apparent specific volumes of AOT in the reverse micelle and the quasi-component water/AOT in the microemulsions with different R at various concentrations are deduced from the density data and used to examine the volumetric properties of the surfactant and water both in the droplets and in the continuous phase, to discuss the droplet interaction, and to determine the critical micelle or microemulsion concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…E ij -van-der-Waals constant in kcal mol E el = Σ i Σ j q i q j /4πε r ij (9) q i -partial charge of the atom i, r ij -interatomic distance between atoms i and j, ε -dielectric constant…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Therefore, an easy and reliable experimental determination of micellar aggregation number is of particular interest. A number of physical methods have been used for the determination of micelle aggregation number such as NMR spectroscopy [6,7], static light scattering (references in the text below), small-angle neutron scattering [8][9][10], small-angle X-ray scattering [11], fluorescence probing methods, and electron paramagnetic resonance [8,[12][13][14][15][16]. Some of them are limited to the aggregation number determination at the surfactant concentration equal to CMC which only provides aggregation number values for isolated non-interacting particles.…”
Section: Introductionmentioning
confidence: 99%
“…properties of surfactants, both in the micellar and monomeric states [8][9][10][11][12][13]. However, only a few studies of the volumetric properties of reverse micelles [14], and no volumetric studies of mixed reverse micelles, have been reported.…”
Section: Introductionmentioning
confidence: 99%